KUALITAS PELAYANAN WAITER DAN WAITRESS TIRTA AYU RESTORAN PADA HOTEL ARYADUTA PEKANBARU - Fathia Adilla; Syofia achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research aims to The serving quality of waiter and waitress of Tirta Ayu restaurant at Aryaduta hotel Pekanbaru.This research was used quantitative method toexamined the issues. The sample in this research are 100 people with use accidental Sampling as a method. Meanwhile this research data accumulation technique was used quisnionare, observation, and documentation. Questionnaire measuring technique of this reaseach was used Likert Scale, then the data will processing by quantitative method with numeric result that orientations at clear and certain conclusion.Based on the research that has been done, The serving quality of waiter and waitress of Tirta Ayu restaurant at Aryaduta hotel Pekanbaru was Good.Keywords: Restaurant, Service of quality, Food And Beverage, Aryaduta Hotel